Lunar Crustal Magnetization Sourced via the Delivery of Iron-rich Ejecta from Basin-forming Impacts - R. I. Citron; L. L. Hood; S. T. Stewart (The Planetary Science Journal, 2025)
The reason for the prevalence of crustal magnetic anomalies within a lunar crust composed of materials that do not retain strong magnetization remains an unresolved question in lunar science. Delivery of iron-rich material from basin-forming projectiles could potentially explain the origin of regions of lunar crust rich in magnetic carriers and the distribution of such regions antipodal to large lunar impact basins. However, the likelihood of projectile material being deposited antipodal to the impact site during basin-forming impacts remains unexplored for a wide range of impact parameters. In this work, we examined the post-impact distribution of iron-rich projectile ejecta from a wide range of lunar basin-forming impacts. We found antipodal ejecta deposits were sufficiently thick to explain magnetic anomalies for impacts with v = 12 km s ^−1 or 16 km s ^−1 , θ = 30° or 45°, and D = 100–250 km, although such impacts also produced significant near-basin ejecta deposits.